Трансляторна еквівалентність фразеологізмів (на матеріалі перекладів Ю. Прохаська) - Ткачівська, Марія Романівна; Tkachivska, M. R. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті розглянуто проблему перекладу фразеологізмів на матеріалі перекладів Ю. Прохаська, здійснено огляд наукових розвідок, подано семантичну класифікацію фразеологізмів і вказано способи їх перекладу. Проаналізовано відтворення фразеологізмів повним і відносним еквівалентом, а також їх часткове відтворення. У висновках вказано отримані результати стосовно використаних перекладачем способів перекладу. The paper explores the problem of rendering phraseological units viewing scientific investigations concerned. The analysis of the issue under study is pursued, semantic classification of phraseological units is presented, the ways of their translation are given. The basic material is set forth with illustrative examples added, and the findings are substantiated. The analysis deals with interpretation of phraseological units by means of using complete and relative equivalent correspondences, as well as their partial identity. The study is based on translations by Yurko Prokhasko. The conclusion highlights findings concerning the methods of translation used by the interpreter.
Translation Equivalents of Phraseological Units (based on translations by Yu. Prohaskо
Keywords: переклад; interpretation; фразеологізм; phraseological unit; класифікація; classification